2020
DOI: 10.14336/ad.2020.0216
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of SIRT1 in Parkinson’s Disease: Mechanism and Therapeutic Considerations

Abstract: Silence information regulator 1 (SIRT1), a member of the sirtuin family, targets histones and many non-histone proteins and participates in various physiological functions. The enzymatic activity of SIRT1 is decreased in patients with Parkinson's disease (PD), which may reduce their ability to resist neuronal damage caused by various neurotoxins. As far as we know, SIRT1 can induce autophagy by regulating autophagy related proteins such as AMP-activated protein kinase, light chain 3, mammalian target of rapamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 159 publications
(143 reference statements)
1
64
0
Order By: Relevance
“…Another toxic effect elicited by Sphk1 inhibition and "sphingolipid biostat" disturbances is oxidative stress. Therefore, anti-oxidative agents, like Sirt1 activators, may be significantly promising in PD therapy, since Sirt1 may also reduce ASN accumulation by regulating its autophagy [181,182].…”
Section: Asn-protein Network and Its Role In Neurotoxicitymentioning
confidence: 99%
“…Another toxic effect elicited by Sphk1 inhibition and "sphingolipid biostat" disturbances is oxidative stress. Therefore, anti-oxidative agents, like Sirt1 activators, may be significantly promising in PD therapy, since Sirt1 may also reduce ASN accumulation by regulating its autophagy [181,182].…”
Section: Asn-protein Network and Its Role In Neurotoxicitymentioning
confidence: 99%
“…Resveratrol (trans-3,4′,5-trihydroxystilbene) is a polyphenol present in large amount in red wine, for which many pharmacologic properties, as well as cardioprotection, antioxidant and anticancer activity, are associated with its beneficial effects. It has been widely reported that this polyphenol is correlated with neuroprotective properties both in vitro and in vivo and has been also proposed to exert anti-inflammatory effects in several systems by inducing the expression of sirtuin1 (SIRT1), including in activated microglia [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial biogenesis is a key process in the maintenance of mitochondrial mass, SIRT1 is the main regulator of mitochondrial biogenesis ( Mao et al, 2020 ). The increase of SIRT1 has been considered as a therapeutic strategy for PD, previous research showed that SIRT1 has neuroprotective effects in both in vivo and in vitro PD models ( Li et al, 2020 ). Simultaneously, SIRT1 was significantly downregulated in neurons treatmented with rotenone or MPP + ( Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%